Food security in the 21st century and the role of biotechnology - Pinstrup-Andersen, Per; Cohen, Marc J. (Emerald Publishing Limited, 1999)
Although global food production has consistently kept pace with population growth, the gap between food production and demand in certain parts of the world is likely to remain. More than 800 million people in developing countries lack access to a minimally adequate diet. Continued productivity gains are essential on the supply side, because global population will increase by 73 million people a year over the next two decades. In this article we assess the current global food situation, look at the prospects through to the year 2020, and outline the policies needed to achieve food security for all. Emphasis is on the role that agricultural biotechnology might play in reaching this goal.